(untitled) (Pesquisa Odontológica Brasileira, 2002)
The aim of this study was to investigate the existence of correlation between the TNM clinical classification, histologic malignancy grading and anatomical location of oral squamous cell carcinoma. A total of 120 oral squamous cell carcinomas were selected from the files of the Dr. Luiz Antonio Hospital (Natal, Rio Grande do Norte, Brazil). Data concerning TNM clinical classification and anatomical location of lesions were obtained. Histologic malignancy grading was carried out following the criteria defined by Wahi22 (1971). Pearsons correlation test was applied for the statistical analysis of data. It revealed a statistically significant correlation (r = 0.2993, p = 0.01) between TNM clinical classification and histologic malignancy grading. It also revealed correlation between TNM classification and the anatomical location of oral squamous cell carcinomas (r = 0.4463, p = 0.01). We concluded that TNM classification presented correlation with histological grading and with the different anatomical locations of oral squamous cell carcinomas.